Contemporary fashion illustration techniques - Watanabe, Naoki, 1963- (Beverly, Mass. : Rockport Pub., 2009)
Thoroughly describes the basics of fashion illustration, and covers the latest trends such as vivid images, sprightly movement, and garment material texture.--From publisher description.
1. The basics of fashion design drawing : Body proportion ; Drawing the head ; Drawing arms and legs ; Poses -- 2. Dressing technique : Dressing -- 3. Coloring technique : Coloring ; Patterns ; Materials ; Drawings of various materials ; Processing by computer -- 4. Exercise by garment item : Technical drawing ; Technical drawing steps ; Technical drawing by computer ; Drawings of various items.
Keywords: Fashion drawing; Fashion design; Drawing -- Technique